Pengaruh Komunikasi Pemasaran Melalui Instagram Produk Pakaian Dyaozha terhadap Minat Belanja Generasi Z di Makassar - Fadhel Thovas Malino; Erniwati Erniwati; Imam Mukti (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2025)
This study aims to determine the influence of marketing communications through Instagram on Generation Z's shopping interest in Makassar, with a focus on dyaozha clothing products. A qualitative approach was adopted, utilizing methods such as observation, documentation, and in-depth interviews with Generation Z consumers. The research participants included shop owners and followers of the dyaozha Instagram account. The findings reveal that marketing communications through Instagram—particularly through the use of engaging visual content, appealing design implementation, and active interaction—play a crucial role in shaping Generation Z's shopping interest. Instagram features such as Stories, Reels, interactive polls, and comment sections enable brands to connect more personally with potential buyers. Attention-grabbing content helps build initial interest, while endorsements and testimonials contribute to trust and credibility. Furthermore, consistent interaction between the brand and followers fosters emotional connection and brand loyalty. These factors collectively influence both interest and purchasing decisions among the Gen Z demographic. The study concludes that dyaozha’s strategic use of Instagram marketing communications has proven effective in influencing the shopping behavior of its target audience. Recommendations for dyaozha include the continuous optimization of Instagram's interactive features—such as Q&A sessions, behind-the-scenes content, and user-generated content campaigns—to sustain engagement and improve conversion rates. Additionally, it is suggested that dyaozha expands its reach by targeting broader market segments and utilizing data-driven content strategies to adapt to evolving consumer preferences. This research highlights the vital role of social media in modern marketing strategies, especially when targeting digitally native audiences like Generation Z.